Parents of children with atopic diseases - experiences with care and the interaction with healthcare professionals over time - Gitte Færk; Elisabeth Søndergaard; Lone Skov; Jacob Pontoppidan Thyssen; Kirsten Skamstrup Hansen; Susanne Reventlow (Scandinavian Journal of Primary Health Care)
Objective To explore how the parents of children with atopic dermatitis and allergic diseases such as food allergy, allergic rhinoconjunctivitis, and asthma experience interactions with the Danish healthcare system over time.Design and methods A qualitative design with individual in-depth interviews. The analysis was inspired by Systematic Text Condensation.Subjects Eleven parents of children with atopic dermatitis and allergic diseases who received treatment at hospitals in the Capital Region of Denmark. The families had experiences of cross-sectoral patient care.Results Despite having the same diseases, the children’s care pathways were very different. Mapping demonstrated the intricacy of care pathways for this group of children. We identified three aspects that impacted interaction with healthcare: responsibility, tasks, and roles. The families experienced care when the distribution of tasks and responsibilities associated with treatment and system navigation were consistent with both their expectations and their actual experiences. At the same time, families frequently experienced limited collaboration between healthcare professionals resulting in perceived fragmented care and an extended role for parents as care coordinators. Families felt cared for when healthcare professionals knew both their biomedical and biographical circumstances, and adjusted the level of support and care in accordance with the families’ particular needs, expectations, and evolving competences.Conclusion We suggest that a possible pathway to improve care may be through a partnership approach as part of family-centered care, with general practitioners having a key role in helping to articulate the individual needs and expectations of each family.